Targeting the Immunoproteasome in Health and Disease - Mundt, Sarah (My University, 2016)
The proteasome is a multicatalytic enzyme expressed in all eukaryotic cells and responsible for the degradation of polyubiquitinated proteins. Thereby, the proteasome regulates protein homeostasis and various biological processes such as transcription, translation, and cell cycle. Due to their global effects on cellular functions and viability, proteasome inhibitors are promising drug targets, however, their application is also associated with multiple undesirable side effects. The expression pattern of immunoproteasomes, which incorporate, compared to standard proteasomes, distinct catalytically active subunits (i.e. low molecular mass polypeptide (LMP)2, LMP7, multicatalytic endopeptidase complex-like (MECL)-1), is restricted to immune cells and short-term inducible at sites of ongoing inflammation. Hence, blocking immunoproteasomes might represent as a novel therapeutic strategy for hematologic malignancies accompanied with reduced toxicity compared to constitutive proteasome inhibition. While the immunoproteasome has long been known to shape the antigenic repertoire presented on major histocompatibility complex (MHC) class I molecules, it was recently reported to play a role in cytokine production, T helper (Th) cell differentiation, and T cell survival. Selective inhibition of the catalytically active immunoproteasome subunit LMP7 was shown to ameliorate the clinical symptoms of autoimmune diseases in vivo and to suppress the development of Th1 and Th17 cells and to promote the generation of regulatory T cells (Tregs) under polarizing conditions in vitro. Although the underlying mechanism of the observed effects of LMP7 inhibition is still unclear, these findings opened a large pool of possible therapeutic indications for immunoproteasome inhibitors. On the other hand, interfering with proteasome activity in immune cells could potentially be accompanied by problems of host defense mechanisms against pathogens. Hence, the aim of this thesis was to characterize the impact of LMP7 inhibition on physiological as well as on pathophysiological immune responses in vivo. Due to its negative impact on Th1 and Th17 differentiation the question whether selective inhibition of LMP7 is able to cure T helper cell-mediated experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis (MS), was addressed in the study described in chapter II. MS is a demyelinating autoimmune disease of the central nervous system (CNS) resulting in neurodegeneration and physical disability of patients. In fact, treatment with ONX 0914, an LMP7-selective epoxyketone inhibitor, attenuated disease progression of myelin oligodendrocyte glycoprotein (MOG)35-55-induced EAE after active and passive immunization and was sufficient to prevent disease exacerbation and relapses in a relapsing-remitting proteolipid-protein (PLP)139-151-induced model. LMP7 inhibition strongly reduced the differentiation of autoreactive T helper cells in the periphery and blocked the infiltration of activated immune cells into the brain and the spinal cord of immunized mice. Thereby, ONX 0914 treatment reduced inflammatory responses in the CNS and prevented tissue damage and neurodegeneration normally leading to MS-like symptoms. These results implicate the immunoproteasome in the development of EAE and suggest immunoproteasome inhibitors as promising drug targets for the treatment of MS. Interestingly, immunoproteasome inhibition does not seem to affect CD8+ T cells to the same extent as CD4+ T cells. For instance, in systemic infection with lymphocytic choriomeningitis virus (LCMV), selective LMP7 inhibition shows a rather modest and T cell epitope-selective impact on the virus-specific cytotoxic T cell (CTL) response and did not interfere with viral clearance in vivo. However, Kremer et al. found, that LMP7-/- mice displayed protracted clinical outcome of LCMV-induced meningitis, a CD8+ T cell-mediated neurodegenerative disease of the CNS. In fact, in the course of the study described in chapter III (1.), it was shown that the lack of LMP7-activity resulted in delayed clinical signs of disease due to a decreased inflammatory infiltration into the brain of intracranial infected mice. Interestingly, we observed that LMP7-deficiency and inhibition affect the pathogenesis of LCMV-induced meningitis in a distinct manner. While ONX 0914 treatment appeared to interfere with CTL responses like interferon (IFN)-γ production, LMP7-deficiency resulted in reduced presentation of GP33-41, an immunodominant T cell epitope of LCMV, as well as in decreased expression of several adhesion molecules important for CNS trafficking on CTLs. However, these findings support the important role of LMP7 in immune responses and suggest immunoproteasome inhibition as a novel strategy against inflammation-induced neuropathologies of the CNS. Intracranial LCMV infection is a widely used animal model to study virus-induced CTL-mediated meningitis and immunopathology. Nevertheless, this model causes severe pain and distress in mice, especially at later stages of the disease. For purposes of animal welfare and refinement of this mouse model, the influence of buprenorphine, an opioid derivative, on the LCMV-specific immune response inducing CNS inflammation was determined in the course of the study described in chapter III (2.). Interestingly, although buprenorphine treatment strongly reduced symptoms of pain, which are usually used to estimate the pathological development of this model, the LCMV-specific cytotoxic T cell response and immune cell infiltration into the CNS were not altered in analgesia treated mice. Taken together, this study demonstrated that continuous buprenorphine treatment improves animal welfare without affecting the immune response required to mediate disease pathogenesis in this model for meningitis. The study described in chapter IV investigated the influence of ONX 0914 treatment on allograft rejection in an established MHC-mismatched (C57BL/6 (H-2b) to BALB/c (H-2d)) model of skin transplantation in vivo. Since Th1 and Th17 cells are detrimental and Tregs are critical for transplant acceptance, it was hypothesized that ONX 0914 treatment would interfere with allograft rejection. However, despite reduced allospecific IL-17 production of T cells in vitro, neither ONX 0914 alone nor as a combination therapy with low dose cyclosporine A was able to influence the survival of C57BL/6 derived tail skin grafts on the back of BALB/c recipients. Hence, selective inhibition of the immunoproteasome is not effective in prolonging skin allograft survival in a fully mismatched skin allograft transplantation model. In the course of the study described in chapter V, it was assessed whether immunoproteasome inhibition does also interfere with T helper cell differentiation during systemic infection with Candida albicans since CD4+ T cells play a key role in antifungal immunity. In fact, selective LMP7 inhibition resulted in reduced IL-17 and IFN-γ production in response to C. albicans in vitro and in vivo. ONX 0914 treated mice displayed an exacerbated clinical outcome in ONX 0914 compared to vehicle treated mice which manifested at very early time points postinfection. This finding implied an impact of immunoproteasome inhibition in systemic candidiasis apart from blocking T helper cell differentiation. Interestingly, analyzing cellular infiltration of the brain and the kidney of ONX 0914 treated mice revealed increased neutrophil numbers, a cell type which is known to mediate immunopathology and tissue damage in this model. Accordingly, these mice displayed symptoms of renal failure and sepsis accompanied by increased weight loss and mortality compared to the vehicle treated control group. Taken together, the studies described in this thesis demonstrate the impact of the immunoproteasome on physiological as well as on pathophysiological immune responses. However, in order to estimate the efficacy or potential side effects of selective LMP7 inhibition in immune-mediated diseases it is very important to solve the mechanistic impact of immunoproteasome inhibition on cellular functions in future studies.
Keywords: Immunology; 570